การใช้กระบวนการ เอ ไอ ซี ในการสื่อสารเพื่อการมีส่วนร่วมของตัวแทนจากกลุ่มอาชีพ ในกระบวนการจัดทำแผนพัฒนาเศรษฐกิจและสังคมแห่งชาติ ฉบับที่ 8 (พ.ศ.2540-2544) - กัญญารักษ์ ศรีทองรุ่ง (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
The objectives of this study are four-fold: to analyze the process of AIC (Appreciation-Influence-Control), which was the communication technique used to facilitate a regional seminar on the formulation of the Eight National Economic and Social Development Plan (1997-2001); to examine actual participation among representative groups in the Eight Plan; to identify the strengths and weaknesses of, as well as constraints on, the technique; and to recommend techniques used to support participation in the formulation of national plans. Data were collected through a series of in-depth interviews with five leaders who applied AIC technique and 25 representatives of occupational groups who participated in the regional seminar, comprising community members, developers, academics, businessmen, and government officials. This study concluded that the AIC process facilitated and improved participation in planning, using the strength of recognition, relationships, and management. Five stages in creating dialogue through exercises designed to gain participation were identified. Each stage involves individual thinking, small and larger group assessment, and the feedback through a variety of communication methods. The communication results indicated that non-leader and less-educated groups were passive audience; gender and age made the slightest difference to communication outcome; and unfamiliarity created the condition for listening, but also kept participants aloof at the beginning of the communication process. Strategic factors determining teh ability to speak out included an expression of loving kindness, understanding, favoring democracy, systematic and positive thinking, and simple and friendly environment which corresponds to Buddhism. Participants at the regional seminar on the Eight National Development Plan spoke in favor of continual involvement of the public in the process of national plans formulation. The process could be expanded to include all stakeholders who were valid representatives, men of vision, and outspoken. They also advocated the AIC process, with improvement in stages and methods of communication. To ensure effective involvement, the study found it useful to organize small-group meetings (e.g., at the provincial level, among occupational groups) where group representatives would then be selected to participate in regional seminars.